Anticipating food crises in the Sahel: A methodology for integrating climate and conflict risks into food crises early warning systems in the Sahel - Sarzana, Carolina; Ouedraogo, Yacouba; Minoarivelo, Henintsoa Onivola; Hounnou, Emmanuel Fèmi; Craparo, Alessandro; Sib, Ollo; Doehnert, Federico; Ndiaye, Marie; Samake, Alioubadara; Samb, Cheikh; Akakpo, Koffi (Bioversity International and International Center for Tropical Agriculture, 2025)
Current food crises early-warning systems do not sufficiently integrate predictive conflict and climate signals in a systematic way. To enhance anticipatory capacity within the CH analytical process and strengthen humanitarian assistance, CGIAR and WFP have jointly developed the Conflict–Climate Pressure Index (CCPI), a forward-looking decision-support tool that improves the early detection of aggravating factors driving IPC Phase 3+ food crises.